INTERNATIONAL ECONOMIC INTEGRATION OF UZBEKISTAN: PROCESSES OF ACCESSION TO THE WORLD TRADE ORGANIZATION AND THE EAEU - Turaeva Ugiloy Giyosovna; Mirzaev Mirzabek Abdullaevich (Modern American Journals, 2025)
This article describes the importance of economic integration, the economic integration of Central Asian countries, and the problems in the process of the Republic of Uzbekistan's accession to international financial organizations such as the World Trade Organization and the Eurasian Economic Union.
Keywords: Trade tariffs, integration, foreign trade balance, investment, GATT, Eurasian Economic Union, strategy, product cost, labor migration.